Fostering STEM Interest for Engineering: Determinants Impacting Additional Mathematics Enrollment in East-Coast Malaysia - Chuan, Zun Liang; David Chong, Teak Wei; Akhmedov, Anvarjon; Leong, Teng Man; Tan, Ee Hiae; Aryssa Aqilah, Hamizul (UKM Press, 2025)
In the 21st-century digital economy, the demand for skilled Science, Technology, Engineering and Mathematics (STEM) professionals, including engineering talent, is at an all-time high. However, Malaysian STEM education has witnessed a significant decline in enrolment, reflecting a global trend of waning interest in STEM subjects among students since their early schooling. One of the key determinants impacting the enrolment of upper-secondary students in STEM is mathematics achievement, particularly in Additional Mathematics, which plays a vital role in preparing students for tertiary mathematically oriented engineering programs. Alarming statistics from the Pahang State Education Department reveal a sharp drop in enrolment for Additional Mathematics. This study’s primary objective is to identify the significant determinants impacting the enrolment of urban upper-secondary students in Additional Mathematics in the Kuantan District, especially among the first cohort to experience the revised Kurikulum Standard Sekolah Menengah (KSSM) since 2017. Utilizing the Cross Industry Standard Process for Data Mining (CRISP-DM) data science methodology, empirical findings underscore the importance of educational discipline, gender, PT3 mathematics achievements, mathematics self-efficacy, peer influence, and teacher influence as key determinants shaping enrolment decisions among urban secondary students in Additional Mathematics. These insights offered valuable guidance for policymakers, highlighting the urgency of STEM education initiatives. Furthermore, they could emphasize the need to empower teachers and counselors in guiding students toward STEM careers in the digital economy and promote gender equality in STEM fields through curriculum enhancements, adjusted teacher expectations, improved educational tracking, and supportive peer interactions.